A Six Sigma and DEA Framework for Quality Assessment in Banking Services - Enrique Delahoz-Domínguez; Adel Mendoza-Mendoza; Rohemi Zuluaga-Ortiz (Administrative Sciences)
This study proposes a methodology that combines Six Sigma and Data Envelopment Analysis (DEA) to measure the quality of banking services. The proposed framework emphasizes seven essential quality dimensions: prompt response, efficient channels, fraudulence, processes, dependable service, credibility, customer satisfaction, and risk management. Integrating both techniques enables a holistic approach to quality evaluation and provides valuable information for the banking industry’s continual improvement. To validate the properties of the methodology, we developed a case study involving 25 Colombian banks. Using Six Sigma metrics, DEA models, and slacks analysis, the results provide a comprehensive study of the quality performance, identifying each bank’s relative strengths and weaknesses in several quality dimensions. The data indicate that some banks perform better on quality characteristics such as customer happiness, dependable service, and procedures. However, this study also reveals a promising finding: banks still have the potential for development, particularly in their response time, channel efficiency, fraud, and credibility, offering hope for the future of banking services.